Chemical Composition and Antibacterial Activity of Bunium persicum From West of Iran - REZA TALEI, GHOLAM; MOSAVI, ZAHRA (Asian Journal of Chemistry, 2010)
Volatile constituents of Bunium persicum seed was obtained by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC-MS). A total of 19 compounds accounting for 95.16 % of the black cumin (B.l) extracted by HD were identified as: γ-terpinene (5.6 %), isopulegol acetate (24.64 %), α-pinene (5.16 %), anethole (20.36 %) and camphor (10.43 %), were the major compounds identified. The oils were examined for the first time, for antibacterial activities against some standared bacteria by broth microdilution method. The extracts showed significant antibacterial activities against Staphylococcus aureus, Escherichia coli and Staphylocuccus epidermidis. The results suggest application of the Bunium persicum essential oils as food flavour and preservative.